2014
DOI: 10.1038/npp.2014.314
|View full text |Cite
|
Sign up to set email alerts
|

Individual Variation in the Motivational and Neurobiological Effects of an Opioid Cue

Abstract: A discrete cue associated with intravenous injections of cocaine acquires greater control over motivated behavior in some rats ('signtrackers', STs) than others ('goal-trackers', GTs). It is not known, however, if such variation generalizes to cues associated with other drugs. We asked, therefore, whether a discrete cue (a light) associated with the intravenous administration of an opioid drug (the shortacting mu receptor agonist, remifentanil) acquires incentive motivational properties differently in STs and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
114
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(124 citation statements)
references
References 49 publications
7
114
3
Order By: Relevance
“…Further supporting this idea, we found that (1) all rats learned a conditioned orienting response to the lever-CS sound (consistent with Yager et al 2015; F (2,13) ¼ 0.52, P ¼ 0.61, subset video analysis, data not shown), and (2) covering the lever did not increase food cup approach during inter-trial-intervals (group effect, F (2,27) ¼ 1.09, P ¼ 0.35; lever availability effect, F (1,27) ¼ 3.94, P ¼ 0.06; Group × Lever availability interaction, F (2,27) ¼ 0.12, P ¼ 0.89; two-way between-within ANOVA). Thus, all rats responded to the predictive lever sound, even when the lever was not visible.…”
Section: Conditioned Approach For Gt Rats After the Lever Was Coveredsupporting
confidence: 73%
See 1 more Smart Citation
“…Further supporting this idea, we found that (1) all rats learned a conditioned orienting response to the lever-CS sound (consistent with Yager et al 2015; F (2,13) ¼ 0.52, P ¼ 0.61, subset video analysis, data not shown), and (2) covering the lever did not increase food cup approach during inter-trial-intervals (group effect, F (2,27) ¼ 1.09, P ¼ 0.35; lever availability effect, F (1,27) ¼ 3.94, P ¼ 0.06; Group × Lever availability interaction, F (2,27) ¼ 0.12, P ¼ 0.89; two-way between-within ANOVA). Thus, all rats responded to the predictive lever sound, even when the lever was not visible.…”
Section: Conditioned Approach For Gt Rats After the Lever Was Coveredsupporting
confidence: 73%
“…However, in the Boakes (1977) study the food cup was occluded by a flap covering the food cup aperture, which may have enhanced the salience of the lever-CS despite its lack of movement. But a light CS does support the acquisition of sign-tracking in pigeons (Silva et al 1992), and in rats when paired with a drug US Yager et al 2015).…”
Section: Discussionmentioning
confidence: 87%
“…Importantly, there is a wide variation in the degree to which individuals engage in sign-tracking behavior, thus allowing for a comparison between drug-associated behaviors and the degree to which individuals assign incentive value to predictive cues. Multiple reports have shown that Pavlovian cues associated with the delivery of drugs of abuse acquire greater control over motivated behavior in animals selected for sign-tracking behavior (Saunders et al, 2013;Yager and Robinson, 2013;Yager et al, 2014). This suggests that these animals are more vulnerable to the influence of reward-predicting stimuli, a characteristic which is associated with compulsive and Effects of alcohol use on stimulus-reward learning M Spoelder et al relapsing drug abuse (Milton and Everitt, 2012;O'Brien et al, 1998;Shaham et al, 2003;Stewart et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…The need of test of the predispositions of the police drivers results from the fact that their actions demand the DEVELOPMENT OF SUPPORT SYSTEM OF PSYCHOLOGICAL TESTS 121 orientation in surroundings (Steenbruggen, Borzacchiello, Nijkamp, & Scholten, 2011) and the prediction of both elements of physical surrounding, as well as the actions of others, because the appearance of a vehicle operating on a signal is a special situation which causes chaotic behaviours. It is important to remember that the vehicle is equipped with systems which service, during the steering of a vehicle, requires the divisibility of attention (Yager, Pitchers, Flagel, & Robinson, 2015).…”
Section: Polish Regulationsmentioning
confidence: 99%